Ecocardiographic comprehensive evaluation of OHCM patients treated with percutaneous ASA. (4th February 2022) - Ferreira, V; Garcia Bras, P; Aguiar Rosa, S; Fiarresga, A; Galrinho, A; Moura Branco, L; Cardoso, I; Ramos, R; Castelo, A; Almeida Morais, L; Cruz Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Alcohol septal ablation (ASA) has been widely accepted as an alternative to surgical myectomy in patients with symptomatic obstructive hypertrophic cardiomyopathy (OHCM) despite optimal medical treatment. The aim of this study was to analyse the effect of ASA on anatomical and functional features analysed by echocardiography, as well as its clinical impact. We further evaluated the safety of procedure. Methods and results: Retrospective analysis of consecutive patients submitted to ASA (2009 – 2019) in a single tertiary centre. A dedicated echocardiogram was performed at 3 and 6 months after procedure. Echocardiographic primary endpoint was a > 50% reduction in left ventricular outflow tract (LVOT) gradient (the definition used for successful procedure). Echocardiographic secondary endpoint was improvement in mitral regurgitation. Clinical primary endpoint was defined as a combined endpoint of cardiac death or hospitalization during follow-up (FU). 110 patients were included, 66.4% women, mean age 65.1 ± 12.2 years. Functional class NHYA class III/IV, angina CCS class II/III and syncope were present in 87.3%, 52.7% and 10.0%, respectively. Baseline LVOT gradients at rest and at Valsalva manoeuvre were 93.6 ± 39.8 mmHg and 118.9 ± 44.2 mmHg. Maximum septal thickness was 21.0 ± 3.3 mm, 24.5% had moderate mitral regurgitation and 52.7% showed systolic anterior motion of mitral valve. During hospitalization for ASA, peak creatine kinase after procedure was 1306 ± 816 U/l. 17 (17.1%) patients required permanent PM due to induction of permanent complete heart block. There was one case of inferior myocardial infarction and one case of cardiac tamponade. Echocardiographic primary endpoint was achieved by 83.6% of patients. At 3 and 6-months follow up, LVOT gradients was significantly decreased in successful comparing with unsuccessful procedure group (24.6 ± 23.9 vs 82.0 ± 28.7 mmHg, p = 0.003 and 31.8 ± 34.5 vs 68.6 ± 27.8 mmHg, p = 0.027, respectively). There was no difference in baseline clinical or echocardiographic parameters between both groups. Regarding the echocardiographic secondary endpoint, among patients with moderate mitral regurgitation, 80% improved to mild regurgitation. A significant reduction in basal septal thickness was achieved in most patients, from 21.0 ± 3.3mm to 16.4 ± 2.7 mm after ASA (p = 0.001). During mean FU of 3.4 ± 2.1 years, clinical primary endpoint occurred in 25.5%, mainly in unsuccessful procedure group (50.0% vs 20.7%, p = 0.013). Reintervention was performed for recurrence of symptoms in 14 (12.7%) patients, surgical myectomy in 3 (3.6%) and repeated ASA in 10 (9.1%). Conclusion: ASA allows a significant reduction in LVOT gradient and improvement of mitral regurgitation in the majority of patients with OHCM. Systematic and comprehensive echocardiographic evaluation assumes a paramount importance for the evaluation of procedural success.